Proposed Design of Sewing Process Improvement to Minimize Polyester Technical Sportswear Product Defect at PT. X Based on The DMAIC Method Approach - Achmad, Fandi; Yustiana Lubis, Marina; Nugrahaini, Yunita (Jurnal Sistem Teknik Industri, 2023)
Various companies want to improve product quality and process speed for customer satisfaction in the current era, including PT. X. Problems at PT. X is the number of defects that exceed the company's tolerance limit. The methodology used is a structured DMAIC method to identify the root causes of defects and resolve them. This study aimed to reduce defects in sportswear products caused by problems in the sewing process. The results showed that the problem in the sewing process was due to the process performance that still did not meet the standard process requirements, so the resulting output did not match the company's specifications. Therefore, it is necessary to design an alarm timer integrated with the sewing machine to minimize the frequency of defects in the sewing process. The design of the alarm timer uses the Reverse Engineering design method, which can minimize defects in the sewing process and increase the capability of the PT. X process.